State-of-the-art of the synthesis and applications of sulfonated carbon-based catalysts for biodiesel production: a review - Chi, Cheng Chong; Yoke, Wang Cheng; Man, Kee Lam; Herma Dina, Setiabudi; Vo, Dai-Viet N. (Wiley-Blackwell, 2021)
Sulfonated carbon-based catalysts (SCC) are favorable heterogeneous acids for acid-catalyzed reactions including esterification and transesterification for biodiesel production. They are covalently functionalized with SO3H groups via CPhSO3H or CSO3H linkages with special carbon structures. To date, the types of SCC for biodiesel production ranges from biochar (BC), activated carbon (AC), graphene, graphite oxides, multiwalled carbon nanotubes, order mesoporous carbon, and graphitic carbon nitride. Lignocellulosic and biomass wastes are important carbon precursors for low-cost BC and AC production. This review critically reviews and summarizes the most up-to-date research progress in the evolution of SCC for biodiesel production. Systematic discussions and comparisons on the different carbon materials, preparation methods, and sulfonation preparation parameters which directly affect the physicochemical attributes and catalytic performance are provided. The applications and reusability studies of these materials in biodiesel production are also included. Finally, the challenges to be addressed and future prospects of the research direction on the applications of SCC for biodiesel production are discussed.